FAKTOR RESIKO TERJADINYA VARISES VENA TUNGKAI BAWAH (VVTB) PADA PRAMUNIAGA DI KOTA SEMARANG - Kuncoro Adi Pratiknyo; Asih Budiastuti; YL Aryoko Widodo (Jurnal Kedokteran Diponegoro, 2016)
Background : Lower Limb Varicose Vein (LLVV) is (a condition where) normal vein (in leg) is dilated because of venous pressure increment. LLVV can create cosmetic problem because of discomfort feeling and unattractive appearance of patient’s leg. (LLVV can create discomfort and cosmetic problem because of unattractive appearance of patient’s leg)